Origin-Specific Adhesive Interactions of Mesenchymal Stem Cells with Platelets Influence Their Behavior After Infusion. (23rd March 2018) - Sheriff, Lozan; Alanazi, Asma; Ward, Lewis S. C.; Ward, Carl; Munir, Hafsa; Rayes, Julie; Alassiri, Mohammed; Watson, Steve P.; Newsome, Phil N.; Rainger, G. E.; Kalia, Neena; Frampton, Jon; et al.
Abstract : We investigated the adhesive behavior of mesenchymal stem cells (MSC) in blood, which might influence their fate when infused as therapy. Isolated human bone marrow MSC (BMMSC) or umbilical cord MSC (UCMSC) adhered efficiently from flow to the matrix proteins, collagen, or fibronectin, but did not adhere to endothelial selectins. However, when suspended in blood, BMMSC no longer adhered to collagen, while UCMSC adhered along with many aggregated platelets. Neither MSC adhered to fibronectin from flowing blood, although the fibronectin surface did become coated with a platelet monolayer. UCMSC induced platelet aggregation in platelet rich plasma, and caused a marked drop in platelet count when mixed with whole human or mouse blood in vitro, or when infused into mice. In contrast, BMMSC did not activate platelets or induce changes in platelet count. Interestingly, isolated UCMSC and BMMSC both adhered to predeposited platelets. The differences in behavior in blood were attributable to expression of podoplanin (an activating ligand for the platelet receptor CLEC-2), which was detected on UCMSC, but not BMMSC. Thus, platelets were activated when bound to UCMSC, but not BMMSC. Platelet aggregation by UCMSC was inhibited by recombinant soluble CLEC-2, and UCMSC did not cause a reduction in platelet count when mixed with blood from mice deficient in CLEC-2. We predict that both MSC would carry platelets in the blood, but their interaction with vascular endothelium would depend on podoplanin-induced activation of the bound platelets. Such interactions with platelets might target MSC to damaged tissue, but could also be thrombotic. Abstract : Bone-marrow mesenchymal stem cells (BMMSC) and umbilical cord mesenchymal stem cells (UCMSC) are both able to bind directly to collagen and fibronectin. However, in blood, BMMSC bind platelets which are inactive and effectively shield them so that they do not adhere to platelets deposited on fibronectin or collagen. UCMSC express podoplanin (PDPN) so that they not only bind platelets but also activated them through CLEC-2. They bind with activated platelets on collagen but do not adhere to the minimally activated platelets on fibronectin. In the flowing blood, the UCMSC with bound platelets may be able to drive wider-spread activation and aggregation of platelets, that leads to a reduction in platelet count in vitro or in vivo.